THE INFLUENCE OF USER GENERATED CONTENT CONSUMER PURCHASE INTEREST WITH DISCOUNTS AS A MODERATING VARIABLE - Nova Ch. Mamuaya; Fitri Novilia; Julinta Paulina; Yeheskial Nggandung; Luthfi Nuraini (ITB AAS Indonesia Surakarta, 2024)
Abstract Reviews from TikTok users can increase market share, increase consumer trust, and ultimately increase consumer purchasing decisions. This research is quantitative research with an exploratory approach. This research collected data by distributing it to 300 TikTok users consisting of 150 consumers and 150 producers, each of whom had carried out the activity at least once. Thus it can be concluded that the data used is primary data. The data used above was analyzed with smart PLS 4.0. The research results show that First,The User Generated Content variable has a positive relationship and a significant influence on the Purchase Interest variable because the more reviews from TikTok users, the greater the seller's market share and the more consumers know about the product. If the product gets good reviews, consumer purchasing decisions will increase. Second, The Discount variable is able to moderate the positive relationship and significant influence of the User Generated Content variable on the Purchase Interest variable, the results are even more significant because good reviews, a large market share and high trust will convince consumers even more if accompanied by a bigger discount. bigger than competitors. Keywords: User Generated Content, Discount, Problem, Consumer Pruchase Interest